Screening of amilolytic bacteria in the digestive tract of Red Snapper (Lutjanus campechanus) as probiotic candidates - Desi Indah Ramadani; Anis Zubaidah; Ganjar Adhywirawan Sutarjo (IJOTA (Indonesian Journal of Tropical Aquatic), 2022)
Fish utilize energy from carbohydrate sources in small amounts because of the low secretion of the enzyme amylase for digestion. One alternative is to increase the availability of exogenous digestive enzymes by utilizing bacteria from the digestive tract that have amylolytic activity. This study aims to isolate amylolytic bacteria in the digestive tract of Red Snapper as a probiotic candidate. This study used several methods, namely amylolytic test on starch, test for resistance to acid conditions (pH 3), observation of bacterial growth for 30 hours, antagonistic test against pathogenic bacteria, test for attachment to the stomach, gram staining test, and pathogenicity test on shrimp. Screening of amylolytic bacteria in the digestive tract of red snapper produced five isolates, namely A1, A2, A3, A4, and A5. From the results of the amylolytic test, only three isolates were further tested, namely A1, A2, and A4. The three isolates were able to survive in acidic conditions of pH 3 and pH 7 for eight hours with density values ​​(OD) in isolates A1 (0.630), A2 (0.597), and A4 (0.601). Isolates A1, A2, and A4 respectively produced antagonistic values ​​with inhibition zones of 8.4 mm, 7.5 mm, and 10.3 mm. Next. the ability to attach bacteria to isolates A1 (6.6 x 102 cfu/ml), A2 (11.8 x 102 cfu/ml) and A4 (16.5 x 102 cfu/ml). After that, the pathogenicity test was carried out aimed at proving that the isolate was not pathogenic to the host. Based on the results of the study, there were three bacterial isolates (A1, A2, and A4) in the digestive tract of red snapper that had met the requirements for probiotic candidates in fish/shrimp and the best was A4 isolate.